34 Laryngeal Transplantation (Laryngeal Cancer, 2019)
Laryngeal transplantation is an exciting option for replacing laryngeal function. There have been three human larynx transplants that have been successful and fully reported. The surgical procedure has been well developed and variations have been described that include transplantation of skin, esophagus, and pharynx. Organ transplantation has several known associated risks and side effects including immune suppression–associated malignancies. These become increasingly important for non–life-sustaining transplants, especially in the setting of prior malignancies such as larynx cancer. Understanding these risks and placing them in the context of quality-of-life goals for patients is important. This chapter will describe the current state of the field and summarize the results of the three transplants previously performed.
Keywords: larynx; trachea; pharynx; esophagus; thyroid; transplant; immunosuppression; function; risks; rejection